Mortality in British vegetarians. - Appleby, P; Key, T; Thorogood, M; Burr, M; Mann, J (2002)
OBJECTIVE: To compare the mortality of British vegetarians and non-vegetarians. DESIGN: Analysis of original data from two prospective studies each including a large proportion of vegetarians--the Oxford Vegetarian Study and the Health Food Shoppers Study. Standardised mortality ratios (SMRs) compared with the population of England and Wales were calculated from deaths before age 90 for vegetarians and non-vegetarians in each study. Death rate ratios (DRRs) for vegetarians compared with non-vegetarians within each study were calculated for each of 14 major causes of death. SETTING: UK. SUBJECTS: Twenty-one thousand men and women aged 16-89 years at recruitment, including more than 8,000 vegetarians. RESULTS: SMRs for all causes of death were significantly below the reference level of 100 in both studies: 52 (95% confidence interval (CI) 49-56) based on 1,131 deaths in the Oxford Vegetarian Study and 59 (57-61) based on 2,346 deaths in the Health Food Shoppers Study. For all causes of death, the DRR for vegetarians compared with non-vegetarians was close to one in both studies: 1.01 (95% CI 0.89-1.14) in the Oxford Vegetarian Study, 1.03 (0.95-1.13) in the Health Food Shoppers Study. CONCLUSIONS: British vegetarians have low mortality compared with the general population. Their death rates are similar to those of comparable non-vegetarians, suggesting that much of this benefit may be attributed to non-dietary lifestyle factors such as a low prevalence of smoking and a generally high socio-economic status, or to aspects of the diet other than the avoidance of meat and fish.